2018
DOI: 10.1002/nafm.10051
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Temporal Trends in Fisheries Abundance Using Bayesian Dynamic Linear Models: A Case Study of Riverine Smallmouth Bass Populations

Abstract: Detecting temporal changes in fish abundance is an essential component of fisheries management. Because of the need to understand short‐term and nonlinear changes in fish abundance, traditional linear models may not provide adequate information for management decisions. This study highlights the utility of Bayesian dynamic linear models (DLMs) as a tool for quantifying temporal dynamics in fish abundance. To achieve this goal, we quantified temporal trends of Smallmouth Bass Micropterus dolomieu catch per effo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Decisions on mitigation strategies rely on integration of vulnerability analyses with the needs of the communities that rely on the managed fishery. Corroborating vulnerability assessment provided by the PSA with local knowledge, trend analyses and extrapolation techniques can give a more complete picture of how to best prioritize research and management efforts (Finkbeiner et al., 2017; Frawley et al., 2019; Mason et al., 2019; Oestreich et al., 2019; Schall et al., 2018). Previous studies employing the existing PSA could benefit from re‐analysis to discover whether management priorities require shifts.…”
Section: Discussionmentioning
confidence: 99%
“…Decisions on mitigation strategies rely on integration of vulnerability analyses with the needs of the communities that rely on the managed fishery. Corroborating vulnerability assessment provided by the PSA with local knowledge, trend analyses and extrapolation techniques can give a more complete picture of how to best prioritize research and management efforts (Finkbeiner et al., 2017; Frawley et al., 2019; Mason et al., 2019; Oestreich et al., 2019; Schall et al., 2018). Previous studies employing the existing PSA could benefit from re‐analysis to discover whether management priorities require shifts.…”
Section: Discussionmentioning
confidence: 99%
“…Health issues, including mortality events of young-of-year (Smith et al, 2015;Walsh et al, 2018), as well as skin lesions (Blazer et al, 2020), a high prevalence of intersex (testicular oocytes; TO), and other signs of exposure to endocrine disrupting contaminants in adults (Blazer et al, 2014a) have been observed there. These have not only raised concerns of resource managers and the public but have also been associated with population declines (Schall et al, 2018a;Smith et al, 2015). To date, no single cause for the health anomalies has been identified; rather, poor water quality, complex mixtures of contaminants, and various pathogens and parasites have been identified as potential risk factors (Boonthai et al, 2018;Schall et al, 2018b;Walsh et al, 2018).…”
Section: Introductionmentioning
confidence: 99%